2020
DOI: 10.3390/ijerph17239034
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Quality of Life of Women One Year after Maternal Near-Miss in Low and Middle-Income Countries: The Case of Zanzibar, Tanzania

Abstract: Women who experienced a maternal near-miss are at risk of mental health complications and lower quality of life, but long-term consequences are largely unknown. The aim of this study is to assess whether mental health symptoms and quality of life change over time and to examine associations with risk factors among post-partum women. In this cohort study, women with maternal near-miss were matched to women without or with mild complications at Mnazi Mmoja Hospital in Zanzibar. Depressive and post-traumatic stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(41 reference statements)
2
6
0
Order By: Relevance
“…The finding of our study also showed that women who had vaginal delivery were more likely to belong to the lower HRQOL trajectories in all HRQOL domains relative to the highest trajectories. This is in line with the study finding in Tanzania which reported that women who had caesarean delivery were more likely to have better physical HRQOL scores than their counterparts 62. Another study in Asia also reported that women who had planned caesarean sections have higher scores in all the domains of HRQOL than mothers who had spontaneous delivery or instrument-assisted delivery 67.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The finding of our study also showed that women who had vaginal delivery were more likely to belong to the lower HRQOL trajectories in all HRQOL domains relative to the highest trajectories. This is in line with the study finding in Tanzania which reported that women who had caesarean delivery were more likely to have better physical HRQOL scores than their counterparts 62. Another study in Asia also reported that women who had planned caesarean sections have higher scores in all the domains of HRQOL than mothers who had spontaneous delivery or instrument-assisted delivery 67.…”
Section: Discussionsupporting
confidence: 89%
“…Some of these complications the authors reported were hypertensive disorders and postpartum haemorrhages. It has been also reported by other studies that intercurrent illness and gestational hypertension lead to lower HRQOL in postpartum women 61 62…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Also, lower income was associated with poorer HRQoL after childbirth 21 , 22 . Level of education also affects the HRQoL 16 , 23 , with lower education levels in women significantly associated with a lower HRQoL 16 . In contrast, some studies have reported that higher education was significantly associated with a lower HRQoL 14 , 24 .…”
Section: Introductionmentioning
confidence: 99%